Articulating the Brand Value through Storytelling: Case Study of Oseng Balayar Company - Rabbani, Rahmi; Aldianto, Leo (Journal of Business and Management Review, 2024)
Research Aims: A decrease in a company's sales can occur due to customer awareness of brand value. Creating a good brand value requires relevance to customer's needs and desires. However, creating brand value will only be successful if communicated well. This research aims to propose a brand communication strategy through storytelling to articulate the brand value. Design/methodology/approach: The methodology of this research use qualitative research methods which collected using the interview method conducted with nine customers, referring to the saturation method for the number of respondents. The data analysis of this research uses thematic analysis to understand the value proposition of customers and create company value related to customers, followed by business model innovation analysis using the business model canvas tools to capture and articulate the company's external value obtained from a customer perspective and combined with the company's internal values. Research Findings: This research uses the Oseng Balayar case study because this company has products with cultural values ​​and culinary heritage that can be communicated through storytelling. The results of this research are proposals for a storytelling concept that become a brand communication tool to increase customer awareness and engagement. Theoretical Contribution/Originality: The design of the storytelling concept was found through the slow storytelling method to articulate the company's value using value proposition and business model analysis. Keywords: Brand Value, Brand Communication, Value Proposition, Business Model Innovation, Brand Storytelling.